EFL Students' Preference on Seating Arrangement in Speaking Class - Raodahtul Jannah; Sitti Nurfaidah (AL LUGHAWIYAAT, 2021)
This study aims to identify students' choice for seating arrangement in speaking class.The researcher uses qualitative design. As a result this study focuses on students’ preference on seating arrangement in speaking class. The researcher conducted a case study involving 19 participants of the third semester at the English Education Study Program in IAIN Kendari and gathered data from observation, students’ reflection and questionnaire.The finding show that 72% buzz group seating, 10% horseshoe seating, 5% traditional seating, 5% pair seating, and 8% cluster seating. This study implies that seating arrangement help the students’ focus and interest in learning process, participating and engaged in cooperative learning. Therefore, improve their language skills to interact with each other in a more fluent way. Keywords: Seating arrangement, Speaking Class